2009
DOI: 10.1039/b822385h
|View full text |Cite
|
Sign up to set email alerts
|

Rational design and applications of highly efficient reaction systems photocatalyzed by noble metal nanoparticle-loaded titanium(iv) dioxide

Abstract: The fundamentals and applications of TiO(2) photocatalysis have been extensively studied in recent decades, the central theme being increasing reaction efficiency. A guideline for achieving so-called "reasonable delivery photocatalytic reaction systems (RDPRSs)" has been presented. This tutorial review summarizes recent developments in the RDPRS-based design of highly efficient photocatalytic reactions by noble metal nanoparticle-loaded TiO(2) (M/TiO(2)). After introducing the conditions required for RDPRSs, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
224
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 321 publications
(228 citation statements)
references
References 36 publications
2
224
0
2
Order By: Relevance
“…A number of studies 7,8,16,44,48,49,59 have already shown the importance of the lattice defects in conjunction with PCA either in the case of pristine or heterojunction catalysts, where they can be identied through optical properties. We have performed PL spectroscopy on the CSHJ nanobers (Fig.…”
Section: Photocatalytic Activity Of Core-shell Heterojunction Nanobersmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies 7,8,16,44,48,49,59 have already shown the importance of the lattice defects in conjunction with PCA either in the case of pristine or heterojunction catalysts, where they can be identied through optical properties. We have performed PL spectroscopy on the CSHJ nanobers (Fig.…”
Section: Photocatalytic Activity Of Core-shell Heterojunction Nanobersmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Understanding the catalysis mechanism is vital for the design of new functional materials to be a part of an environmentally friendly technology. The catalytic process on the surface of a semiconductor has been proposed by Izumi et al 12 and Matthews.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] However, to increase the efficiency of a semiconductor catalyst one needs to isolate 4 or at least delay the recombination of photogenerated electrons and holes. 1,[5][6][7][8][9][10][11][12][13] To achieve this, lattice defects are induced in the semiconductor 1,6,[8][9][10][11][12][13] in addition to the fabrication of heterojunctions (either with noble metals [5][6][7] or another semiconductors 4,14 ). In connection to lattice defects, depending on the type and energetic location of the defect, their character is determined to capture either an electron or a hole, thereby delaying the recombination process.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Note that the controllability of the defect density depends on the type of defect and the semiconductor itself. 1,6,[8][9][10][11][12][13] In the context of ZnO, numerous studies deal with V O s, 4,8,10,11,13,21 which is not the case with Zn i s. It is also notable that the balance between the relative densities of Zn i s and V O s is still challenging. 15 The presence of Zn i s and V O s in ZnO can be easily identied by simple photoluminescence (PL) experiments, [15][16][17]27 indicated by blue and green emissions, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation